Comparison of the effectiveness of emotion-oriented couple therapy and structural couple therapy on marital justice and relationship maintenance strategies in conflicting couples - Ansari , Zohreh; Naderian , Fariba; Gol abedini , Fatemeh; Yavari Kermani , Maryam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of emotion-oriented couple therapy and compare it with structural couple therapy on marital justice and relationship maintenance strategies in conflicting couples. Method: The present study was a quasi-experimental with pre-test and post-test with a two-month control and follow-up group; The statistical population of the present study was 205 couples referring to counseling centers in Shiraz in the last six months of 1399. After screening with the Sanai Marital Conflict Questionnaire (2008), 60 couples who received more than 150 points from the cut-off point were selected by available means. They answered the Marital Justice Questionnaire and Relationship Strategies (Stafford, Dinton and Haas, 2000) and in the experimental group of emotion-focused couple therapy (10 couples), the experimental group of structural couple therapy (10 couples) and the control group (10 couples) were randomly replaced. Both experimental groups underwent Johnson (2004) emotion-focused couple therapy and Minochin (1974) structural couple therapy intervention for eight 90-minute sessions, and the control group did not receive any intervention. Data were analyzed using repeated measures mixed variance analysis. Results: The results showed that emotion-oriented couple therapy (F = 8.97 and P = 0.005) and structural couple therapy (F = 10.04 and P = 0.003) on increasing marital justice and emotion-oriented couple therapy (0.60). F = 59 and P = 0.001) and structural couple therapy ‌ (F = 19.29 and P = 0.001) are effective in maintaining relationship strategies in conflicting couples and this effect was stable in the follow-up phase; The results of post hoc test also showed that the difference between the two groups of emotion-oriented couple therapy and structural couple therapy in marital justice variables and strategies for maintaining the relationship is not significant. Conclusion: The results of the research suggest evidence that the intervention of emotion-oriented couple therapy and structural couple therapy is a suitable method for increasing marital justice and relationship maintenance strategies in spouses suffering from marital conflict